2018
DOI: 10.1002/jcb.27312
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional regulation of adenosine 5′‐monophosphate–activated protein kinase activity by berberine and metformin in response to changes in ambient glucose concentration

Abstract: Both berberine and metformin are well‐known antihyperglycemic agents for diabetes treatment. Adenosine monophosphate (AMP)‐activated protein kinase (AMPK) activation is often considered as the most important molecular mechanism although the mechanism has been challenged recently. Up to now, when the ambient glucose level changes dynamically, the interaction between AMPK activity and the glucose‐lowering effects of the agents remains largely unknown. To address this issue, HepG2 hepatocytes and C2C12 myotubes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…us, AMPK activation may be caused by the increase in the AMP/ATP ratio due to mitochondrial inhibition [61]. In contrast, other scholars found that BBR stimulated glycolysis and improved sugar metabolism via inhibiting mitochondrial respiratory chain complex I, which did not depend on AMPK activation, in case of nonhypoglycemia [62,63].…”
Section: Promoting Insulin Secretion Bbr Can Promote Insulin Secretion With a Hypoglycemic Effect By Pancreatic β-Cellsmentioning
confidence: 96%
“…us, AMPK activation may be caused by the increase in the AMP/ATP ratio due to mitochondrial inhibition [61]. In contrast, other scholars found that BBR stimulated glycolysis and improved sugar metabolism via inhibiting mitochondrial respiratory chain complex I, which did not depend on AMPK activation, in case of nonhypoglycemia [62,63].…”
Section: Promoting Insulin Secretion Bbr Can Promote Insulin Secretion With a Hypoglycemic Effect By Pancreatic β-Cellsmentioning
confidence: 96%
“…In vitro and in vivo studies have highlighted that BBR contributed to its therapeutic activities via variety of mechanisms and signaling pathways, including improving IR, activating AMPK, modulating gut microbiota, reducing gluconeogenesis in liver and enhancing glycolysis in peripheral tissues 217, 222-224. Although many studies have shown that BBR is an AMPK activator 30, 225, 226, in HepG2 and C2C12 cells BBR promoted glucose metabolism by stimulating glycolysis, and this effect may be independent of AMPK activity 227. A recent study has shown that BBR (150 mg/kg/d, p.o.…”
Section: Bbr In Treating Metabolic Diseasesmentioning
confidence: 99%
“…Meanwhile, numerous experimental studies have shown that BBR ameliorate body metabolic dysfunction through multiple mechanisms ( Yin et al., 2012 ; Ilyas et al., 2020 ). In terms of glucose metabolism, BBR strengthened autophagy and protected from high glucose-related injury in podocytes by promoting the AMPK activation, at the same time, the bidirectional regulation of AMPK activity can reduce the risk of hypoglycemia caused by berberine ( Xiao et al., 2018 ). BBR also through TLR4/MyD88/NF-κB signaling pathway improves gut-derived hormones ( Gong et al., 2017a ), alleviate inflammation by reducing the exogenous antigen load in the host ( Zhang et al., 2012 ).…”
Section: Berberine For Metabolic Disordersmentioning
confidence: 99%